On the taxonomy and nomenclature of the annual species of the Brachypodium distachyon grass complex (Gramineae, Pooideae) - Ferrer-Gallego, P. Pablo; Fabado, Javier; Catalán, Pilar (Phytotaxa, 2025)
The taxonomy and nomenclature of the type material potentially linked to the three recognized annual species of the grass genus Brachypodium (B. distachyon, B. stacei, B. hybridum) have been investigated. We performed a statistical discriminant analysis of twelve quantitative morphological traits on eight herbarium types, corresponding to heterotypic synonyms and newly designated types of each treated name, along with the lectotype and the epitype of B. distachyon, the holotypes of B. stacei and B. hybridum, plus 50 additional representative specimens of the currently recognized taxa. This was complemented by a comprehensive nomenclatural review. The possible taxonomic assignments of types to these names, as well as the nomenclatural priority of Brachypodium distachyon and ten related names: B. hybridum, B. macrostachyum, B. megastachyum, B. stacei, Bromus pentastachyos, Festuca monostachyos, F. rigida, Trachynia platystachya, Triticum schimperi, and T. subtile, have been discussed. Lectotypes are designated for Festuca monostachyos, F. rigida, Triticum schimperi, and T. subtile. Based on our taxonomic and nomenclatural study, the names Festuca monostachyos and Triticum subtile can be considered conspecific and heterotypic synonyms of the Linnaean name Bromus distachyos (≡ Brachypodium distachyon). Furthermore, the names Brachypodium macrostachyum, Brachypodium megastachyum, Bromus pentastachyos, Festuca rigida, and Brachypodium distachyon var. platystachyon (≡ Trachynia platystachya) are conspecific with Brachypodium hybridum, and Triticum schimperi is conspecific with Brachypodium stacei. Since the names B. hybridum and B. stacei are widely used but are later heterotypic synonyms according to results of our study, proposals to conserve these names are necessary. On the other hand, the application of the names Bromus pauper, Brachypodium geniculatum, Festuca pseudistachya, Bromus paradoxus, and Triticum flabellatum is uncertain, and as such, they are treated as nomina ambigua. Finally, Festuca ciliata and Triticum asperum are two illegitimate names, and Triticum brevisetum is recognized as a new synonym of Brachypodium retusum, with a lectotype designated in this paper.